<u><em>Answer:</em></u>
y = 23
<u><em>Step-by-step explanation:</em></u>
Add the numbers:
18 + 5 - y
= 23 - y
Rearrange terms:
y = 23
Answer:
5x − 4 = 3x + 8
5x - 4 <em>+ 4</em> = 3x + 8 <em>+ 4</em>
5x = 3x + 12
5x <em>- 3x</em> = 3x + 12 <em>- 3x</em>
2x = 12
2x <em>/ 2</em> = 12 <em>/ 2</em>
x = 6
Answer:
8
Step-by-step explanation:
Answer:
-8a - 7b - 7c
Step-by-step explanation:
-8a - 2b - 10c - (5b - 3c)
Negate 5b and -3c
-8a - 2b - 10c - 5b + 3c = -8a - 7b - 7c
Cos(x°) = (√3)/2
cos⁻¹[(√3)/2] = x°, that means x° = 30°